Technological Alignment of Teachers in Teaching / Learning on Higher Education: A Case of a Constituent Campus of Tribhuvan University - Ghimire, Shree Prasad; Paudel, Krishna Chandra (Teacher Half-Yearly Journal, 2025)
Information and Communication Technology (ICT) and its use in education is one of the necessary skills for teachers to develop professional skills, knowledge and expertise. In the case of higher education, the use of ICT, particularly, on constituents' campuses is a prominent area in the context of Nepal. This article explores the examination of the university teachers’ access and use of ICT in students' teaching and learning activities. The survey questionnaire was employed to 80 sampled teachers teaching Bachelor and Masters Level in different subjects of one constituent campus of Kathmandu valley. The survey method was applied for the collection of data, analysis and interpretation of the collected data showed that most of the respondents had access to at least one of the ICT facilities at their home but only 35% of the respondents who had access to ICT use it in their teaching and learning activities. By contrast, the majority of the teachers expressed their views they were not excellent at ICT skills. However, only a few teachers needed to learn basic computer skills to use it in their teaching and learning. The findings of this article suggests that the majority of teachers were willing to learn the use of ICT related to classroom instruction effectively.